2016
DOI: 10.1111/iep.12191
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive role of MMP‐9 inhibition along with conventional anti‐tubercular drugs against experimental tuberculous meningitis

Abstract: Tuberculous meningitis (TBM) is an outcome of neuroinflammatory degeneration caused due to Mycobacterium tuberculosis infection and leads to death or neurological disabilities in the affected individuals. It causes the highest morbidity and mortality amongst all forms of tuberculosis. Matrix metalloproteinase-9 levels increase and cause inflammatory destruction during progression of the disease. Although corticosteroids are usually given as an adjuvant therapy to overcome these complications, treatment outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Several animal studies have explored host-pathogen interactions by targeting critical inflammatory pathways implicated in TB pathogenesis (Ong et al, 2014; Ordonez et al, 2016a; Skerry et al, 2012), as well as developing novel adjunctive treatments for TB meningitis (Majeed et al, 2016; Tsenova et al, 2002, 1998). However, these animal models do not evaluate the effect of TB meningitis and the host immune response on normal brain development, which would be crucial in the immature brain.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have explored host-pathogen interactions by targeting critical inflammatory pathways implicated in TB pathogenesis (Ong et al, 2014; Ordonez et al, 2016a; Skerry et al, 2012), as well as developing novel adjunctive treatments for TB meningitis (Majeed et al, 2016; Tsenova et al, 2002, 1998). However, these animal models do not evaluate the effect of TB meningitis and the host immune response on normal brain development, which would be crucial in the immature brain.…”
Section: Discussionmentioning
confidence: 99%
“…25 In agreement with this concept, treatment with Sb-3ct, a specific MMP2 and MMP9 inhibitor, combined with frontline TB antibiotics potentiated bacterial clearance both in vitro and in vivo in a TB meningitis mouse model. 212,213 202,211,215 Due to the hypoxic, acidic and nutrient-poor conditions in granulomas, mycobacterial dormancy is promoted, 25 and while this effectively inhibits bacterial replication, eradication of mycobacteria is greatly hampered because most antibiotics only affect replicating and metabolically active bacteria. Furthermore, poor vascularization hampers drug delivery in granulomas, which is further impaired due to fibrosis and scarring of lung tissue caused by the disease.…”
Section: Granuloma: Formation Angiogenesis and Hypoxiamentioning
confidence: 99%
“…However, this study did not investigate the effect of adjunctive doxycycline treatment with standard anti-TB chemotherapy. Another study reported that administration of SB-3CT; an inhibitor of MMPs, along with conventional anti-TBM drugs significantly suppressed the expression of MMP-9 and enhanced Mtb clearance in a mouse model of TBM ( 63 ).…”
Section: Hdt Targeting the Inflammatory Responsementioning
confidence: 99%